Evaluation of antioxidant properties of soxhlet extraction of Lavandula stoechas L. - Rohollah Hosseini nia fard; Gholam Reza Najafi; Manocheh Fadaeian (بیولوژی کاربردی, 2018)
Lavender (Lavandula angustifolia) is a medicinal plant with essence and belongs to mint family and natively grows in Iran. Its traditionally used for curing joint`s point, cramps, and cold. After recognition and gathering, the Lavender plant was dried in good conditions. After that, using the Soxhlet machine, water solvents, Hexane, and solution of water and ethanol the essence was extracted. After condensing the essence with rotary machine, Spectrophotometer, and finally with GC-MS machine, it was studied and analyzed. In the Hexane extract of the plant Decane, Dodecane, Camphore, Tetradecane, 3-Methylnonane , and 1,8 Cineol had the maximum percentage respectively. Antioxidant activity evaluation with DPPH method showed that the blue extract had the most sensitivity. nce was extracted. After condensing the essence with rotary machine, Spectrophotometer, and finally with GC-MS machine, it was studied and analyzed. In the Hexane extract of the plant Decane, Dodecane, Camphore, Tetradecane, 3-Methylnonane , and 1,8 Cineol had the maximum percentage respectively. Antioxidant activity evaluation with DPPH method showed that the blue extract had the most sensitivity.